Georgia and Abkhazia caught between Turkey and Russia: Turkey's changing relations with Russia and the West in 2015-2016 and their impact on Georgia and Abkhazia - Andrea Weiss; Yana Zabanova (Stiftung Wissenschaft und Politik (SWP), 2016)
Following seven months of severely strained relations, Turkey and Russia began to mend ties in late June 2016, when President Erdogan sent a conciliatory letter to his Russian counterpart. After the attempted coup d'état in Turkey three weeks later, Russian President Putin called Erdogan to express his support, providing added impetus to the normalisation process. By contrast, delayed and cautious reactions by Western leaders, as well as their criticism of the measures taken by the government after the failed coup, have caused disappointment in Turkey, where anti-Western sentiment is on the rise. While these developments have largely been discussed in terms of their implications for the Middle East, they have also affected Turkey and Russia's shared neighbourhood in the South Caucasus, including Georgia and its breakaway region of Abkhazia. The Turkish-Russian crisis called into question Abkhazia's strong ties with the large and active Turkish Abkhaz diaspora, an important economic and societal actor in the defacto state. In Georgia proper, the impact has been more ambivalent, with potential implications for the country's Euro-Atlantic integration processes. (SWP Comments)
Keywords: 320